Formulation and characterization of anti-atherosclerosis drug loaded liquid crystalline nanoparticle - Maslizan, Mardhiah (2022)
Atherosclerosis complications such as myocardial infarction or stroke are among the most rising health concern and remain as the major causes of death that require optimal treatment strategies. The corresponding natural and synthetic anti-atherosclerosis drugs of proanthocyanidin (PAC) and atorvastatin (ATV) which have higher antioxidant properties are known to minimize atherosclerotic plaque progression. Lyotropic liquid crystalline nanoparticles (LLCNPs) recently receive a great deal of interest as a potential drug delivery platform that offers unique self-assembled internal structures, leading to an effective loading and controlled delivery of bioactive materials. Our current research involved formulation and characterization of soy phosphatidylcholine (SPC) and citric acid ester of monoglyceride (citrem), which are employed in the formation of ATVLLCNPs and PAC-LLCNPs. The main objectives of this research are to (1) characterize the crystalline nanostructural properties, polydispersity index (PDI), potential electrical charge on the nanoparticle surface, average particle size, morphological shape characteristics, and potential interaction of ATV-LLCNPs and PAC-LLCNPs (2) evaluate the encapsulation efficiency of ATV and PAC into LLCNPs, (3) analyze the drugs release profile from LLCNPs and (4) investigate the in vitro cell studies of PAC-LLCNPs in macrophage cells. We further showed that varying citrem/SPC content of LLCNPs, ATV-LLCNPs, and PAC-LLCNPs triggers an internal phase of inverse micellar (L2) phase (emulsified microemulsions, EMEs), hexosomes (H2) and biphasic phase (internal H2 phase coexisting with L2 phase). The hexosomes in ATV-LLCNPs and PAC-LLCNPs, with the exception of the CS1:1+ATV system, are structurally stable for 30 days, and there were no noticeable structural alterations for LLCNPs. The lattice parameter also remained stable for a period of 90 days. Smaller range of particle size was observed for the LLCNPs (171.0 to 179.0 nm) as compared to the ATVLLCNPs and PAC-LLCNPs (187.0 to 138.0 nm). The zeta potential of the LLCNPs, ATV-LLCNPs and PAC-LLCNPs produced were -25.4 to -30.3 mV and -18.7 to -27.4 mV, respectively, which suggested that the nanoparticles demonstrate stable colloidal dispersion of LLCNPs system. Differential scanning calorimetry (DSC) analysis of ATV-LLCNPs and PAC-LLCNPs revealed a shift in phase transition, indicating a more stable nanoparticles compared to LLCNPs. Fourier-transform infrared spectroscopy (FTIR) analysis demonstrated the formation of an ester bond between SPC and citrem via the C=C stretch, interactions between phenolic hydroxyl of PAC and carboxylic acid from citrem/SPC via the H-OH stretch, and the interactions between ATV and citric acid from citrem/SPC via the N-H and O-H stretch. ATV and PAC were successfully encapsulated into LLCNPs nanoparticles, which evidences the higher loading efficiency of more than 93% encapsulation in all formulations. The sustained release of ATV-LLCNPs were obtained at 60 % and reached plateau after 5 days, whereas the maximum released of PAC-LLCNPs were obtained at 27% and reached plateau after 2 days, were determined by the pharmacodynamics and pharmacokinetic properties of the respective drug. PAC-LLCNPs, which showed more than 80% cells viability at 150 mg/mL were then proceed for further in vitro test. PAC-LLCNPs demonstrated the presence of lipid droplets (LDs) formation in macrophages cells, in a time-dependent manner. The cytokine studies showed that the PAC-LLCNPs promisingly up regulate the expressions of TNF-α better than the LLCNPs and ATV-LLCNPs samples, due to the differences in viscoelastic behavior of non-lamellar phase LLCNPs. This study proposed the promising stable non-lamellar PAC-LLCNPs as a potential nanocarrier for drug delivery projecting great encapsulation, sustained release and in vitro cellular activities against atherosclerosis complications.